PEMBELAJARAN DIGITAL MULTIMODAL UNTUK MEMBACA PEMAHAMAN INFORMASI SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW DAN BIBLIOMETRIC ANALYSIS - Layinatus Sifa; Elianawati Elianawati; Bambang Subali; Panca Dewi Purwati (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT Reading comprehension is an essential literacy skill that elementary school students need to understand, interpret, and process information from various reading sources. However, students’ low reading comprehension abilities and the suboptimal use of digital learning media remain significant challenges in literacy instruction. This study aims to analyze research trends on multimodal digital learning for improving elementary students’ informational reading comprehension through a Systematic Literature Review (SLR) and bibliometric analysis. The study employed the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method, supported by Publish or Perish, Zotero, and VOSviewer applications. Data were collected from Google Scholar publications published between 2022 and 2026. Through identification, screening, and selection processes based on inclusion and exclusion criteria, 95 articles were selected for analysis. The findings indicate that publications on multimodal digital learning showed fluctuating growth, with the highest number of publications recorded in 2023.Bibliometric analysis revealed several dominant themes, including reading comprehension, digital learning media, media effectiveness, reading comprehension strategies, and innovative technology-based learning models. The review further demonstrates that multimodal digital media and innovative learning models can enhance student engagement, enrich learning experiences, and effectively improve informational reading comprehension skills. Therefore, multimodal digital learning has strong potential as a relevant instructional strategy to support literacy development among elementary school students in the digital era. ABSTRAK Kemampuan membaca pemahaman informasi merupakan salah satu kompetensi literasi yang penting dimiliki siswa sekolah dasar untuk memahami, menginterpretasikan, dan mengolah informasi dari berbagai sumber bacaan. Namun, rendahnya kemampuan membaca pemahaman siswa serta belum optimalnya pemanfaatan media digital dalam pembelajaran masih menjadi tantangan yang perlu diatasi. Penelitian ini bertujuan untuk menganalisis perkembangan penelitian mengenai pembelajaran digital multimodal dalam meningkatkan kemampuan membaca pemahaman informasi siswa sekolah dasar melalui pendekatan Systematic Literature Review (SLR) dan analisis bibliometrik. Penelitian menggunakan metode Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) dengan bantuan aplikasi Publish or Perish, Zotero, dan VOSviewer. Data diperoleh dari Google Scholar pada rentang publikasi tahun 2022–2026. Melalui proses identifikasi, penyaringan, dan seleksi berdasarkan kriteria inklusi dan eksklusi, diperoleh 95 artikel yang dianalisis. Hasil penelitian menunjukkan bahwa tren publikasi terkait pembelajaran digital multimodal mengalami perkembangan yang fluktuatif dengan jumlah publikasi tertinggi pada tahun 2023. Analisis bibliometrik mengidentifikasi beberapa tema dominan, yaitu kemampuan membaca pemahaman, media pembelajaran digital, efektivitas media pembelajaran, strategi membaca pemahaman, dan model pembelajaran inovatif berbasis teknologi. Temuan kajian menunjukkan bahwa penggunaan media digital multimodal dan model pembelajaran inovatif mampu meningkatkan keterlibatan siswa, memperkaya pengalaman belajar, serta mendukung peningkatan kemampuan membaca pemahaman informasi secara lebih efektif. Dengan demikian, pembelajaran digital multimodal berpotensi menjadi alternatif strategi pembelajaran yang relevan untuk mendukung pengembangan literasi siswa sekolah dasar pada era digital.